Modelling of the joint evolution of analysis needs and data warehouse - Brou Assie, Brou; Louis Seka, Louis; Kablan Adou, Jérôme; Oumtanaga, Souleymane (International Journal of Engineering and Technology, 2018)
The decision support system, a set of data, is specifically organized, appropriate and accessible in decision-making. It stems from the data warehouse taking into account the users in this development. However, data warehouse is a complex technology in decision-making systems. Then, we highlight a new approach to the data warehouse model in this paper about the joint evolution of user and data warehouse needs. This model is based on rules combining R-DW (Data-based Data Warehouse) and MDA (Model Driven Architecture) models. As a result, this new approach makes it possible to integrate the knowledge of the users while favoring a temporal evolution of the possibilities of analysis.
Keywords: Decision Support System; Evolution Model; Data Warehouse.